Design And Build The AMANAH Vocational School Main Book Application Using The Waterfall Model - Farabi, Nur Ali; Asymar, Hasta Herlan; Rachmat Hidayat; Setiawan, Dimas Muslim (Journal of Computer Networks, Architecture and High Performance Computing, 2022)
The benefits of information technology in the field of education include improving educational services, facilitating the collection and dissemination of educational information, educational data storage media, improving teaching skills, motivating students, thus helping communication activities in education. The concept of this information system has the effect of transforming the filling of the conventional ledger into digital form, by carrying out this transformation it can affect the easier filling of the master book and secure data storage and a longer time. After the process of accepting new students at SMK AMANAH is completed, the administrative officer or administrative administration enters student data, the value of student report cards per semester into the student master book, the difficulties encountered by administrative officers during the process of entering the data, officers have difficulty in terms of The main book used has a large size and the storage of the master book is still less effective and does not last long because it can be damaged, even though the master book should be able to be used for a long time as a document that is needed at any time. The research method used to design a student master book system is to use the waterfall or waterfall method to produce a design for the school's main book information system (SIBIS). Starting from the login page, the new student registration page, the grade submission page, and reports to help the school.